2022
DOI: 10.1371/journal.pone.0267190
|View full text |Cite
|
Sign up to set email alerts
|

Predicting risks of low birth weight in Bangladesh with machine learning

Abstract: Background and objective Low birth weight is one of the primary causes of child mortality and several diseases of future life in developing countries, especially in Southern Asia. The main objective of this study is to determine the risk factors of low birth weight and predict low birth weight babies based on machine learning algorithms. Materials and methods Low birth weight data has been taken from the Bangladesh Demographic and Health Survey, 2017–18, which had 2351 respondents. The risk factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…Covariates included in our multivariable models were chosen a priori based on relevant literature (Islam Pollob et al 2022 ; Khan et al 2018 ; Kiserud et al 2017 ; Shah et al 2014 ; Tamirat et al 2021 ; Zhou et al 2016 ). Our models included the following potential confounders: maternal age (years), height (cm), weight (kg), education level (six ordered categories), parity ( n ), history of pregnancy loss (yes; no), antenatal attendance (yes; no), iron supplementation (yes; no), infant sex (male, female), household wealth index (quintiles, with first two groups collapsed), average dietary diversity score ( 10 food group scale ), and food security status (food secure; food insecure).…”
Section: Methodsmentioning
confidence: 99%
“…Covariates included in our multivariable models were chosen a priori based on relevant literature (Islam Pollob et al 2022 ; Khan et al 2018 ; Kiserud et al 2017 ; Shah et al 2014 ; Tamirat et al 2021 ; Zhou et al 2016 ). Our models included the following potential confounders: maternal age (years), height (cm), weight (kg), education level (six ordered categories), parity ( n ), history of pregnancy loss (yes; no), antenatal attendance (yes; no), iron supplementation (yes; no), infant sex (male, female), household wealth index (quintiles, with first two groups collapsed), average dietary diversity score ( 10 food group scale ), and food security status (food secure; food insecure).…”
Section: Methodsmentioning
confidence: 99%
“…Birth weight was classified as a binary variable by using a threshold of 2.5 kg at the time of the baby’s birth. If a baby’s birth weight was less than 2.5 kilograms, it is then classified as low birth weight (LBW) [ 69 ]. One additional dummy variable was created to represent the caregivers’ knowledge of dietary diversity, which refers to their understanding of proper nutrition while caring for the child in the absence of the mother.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been conducted in Asia to predict low birth weight in infants. In Bangladesh, a study [3] showed that logistic regression (LR) is more effective than decision tree (DT) in predicting low birth weight (LBW), with an accuracy of 85% using a 70:30 training and test dataset ratio. In India, researchers claim that the Classi cation Tree algorithm had the highest overall prediction accuracy, speci city, AUC, Fvalue, and Precision compared to other classi cation methods, with an accuracy rate of 89.95% [17].…”
Section: Prediction Of Lbwmentioning
confidence: 99%
“…LBW is a major healthcare concern in Bangladesh, with a prevalence rate of 17.7% in 2011, 20% in 2014, and 16% in 2017. Researchers used the chi-square test, DT, and LR models to predict LBW [3]. Evidently, the prevalence of LBW in Bangladesh consistently exceeds 10%, indicating the utmost importance of eradicating this issue.…”
Section: Introductionmentioning
confidence: 99%